Pengaruh Foot Massage terhadap Penurunan Tekanan Darah pada Lansia dengan Hipertensi di Posbindu Gang Saat Rt 05 Rw 23 Kelurahan Kayuringin Kota Bekasi - Khamid, Abdul; Z, M Rahid Algani (Universitas Malahayati, 2025)
ABSTRACT Hypertension, or better known as high blood pressure, is a chronic condition characterized by an increase in blood pressure on the walls of the arteries. This increase forces the heart to work harder in pumping blood throughout the body through the blood vessels. As a result, this can have an impact on blood flow and the health of the blood vessels themselves, which in turn can trigger degenerative diseases. In severe cases, hypertension can result in death (Noerinta, 2020). Data from the World Health Organization (WHO) shows that around 1.28 billion adults aged between 30 and 79 years worldwide suffer from hypertension. According to WHO, 46% of those with hypertension are unaware of their condition, while less than half (42%) are aware that they have the disease. Only about 1 in 5 adults (21%) can successfully control their blood pressure. It is estimated that the prevalence of hypertension, a non-communicable disease, will decrease by 33% between 2010 and 2030. Research Objective: To determine the effect of foot massage on reducing blood pressure in the elderly with hypertension at Posbindu Gang Saat Rt 05 Rw 23 Kayuringin Village, Bekasi City in 2024. This research method adopts a quantitative approach with a correlational analytical research design arranged in a quasi-experimental plan. The method used is